Mode of Action of Glycine on the Biosynthesis of Peptidoglycan - Hammes, W. (1973)
The mechanism of glycine action in growth inhibition was studied on eight different species of bacteria of various genera representing the four most common peptidoglycan types. To inhibit the growth of the different organisms to 80%, glycine concentrations from 0.05 to 1.33 M had to be applied. The inhibited cells showed morphological aberrations. It has been demonstrated that glycine is incorporated into the nucleotide-activated peptidoglycan precursors. The amount of incorporated glycine was equivalent to the decrease in the amount of alanine. With one exception glycine is also incorporated into the peptidoglycan. Studies on the primary structure of both the peptidoglycan precursors and the corresponding peptidoglycan have revealed that glycine can replace l-alanine in position 1 and d-alanine residues in positions 4 and 5 of the peptide subunit. Replacement of l-alanine in position 1 of the peptide subunit together with an accumulation of uridine diphosphate-muramic acid (UDP-MurNAc), indicating an inhibition of the UDP-MurNAc:l-Ala ligase, has been found in three bacteria (Staphylococcus aureus, Lactobacillus cellobiosus and L. plantarum). However, discrimination against precursors with glycine in position 1 in peptidoglycan synthesis has been observed only in S. aureus. Replacement of d-alanine residues was most common. It occurred in the peptidoglycan with one exception in all strains studied. In Corynebacterium sp., C. callunae, L. plantarum, and L. cellobiosus most of the d-alanine replacing glycine occurs C-terminal in position 4, and in C. insidiosum and S. aureus glycine is found C-terminal in position 5. It is suggested that the modified peptidoglycan precursors are accumulated by being poor substrates for some of the enzymes involved in peptidoglycan synthesis. Two mechanisms leading to a more loosely cross-linked peptidoglycan and to morphological changes of the cells are considered. First, the accumulation of glycine-containing precursors may lead to a disrupture of the normal balance between peptidoglycan synthesis and controlled enzymatic hydrolysis during growth. Second, the modified glycine-containing precursors may be incorporated. Since these are poor substrates in the transpeptidation reaction, a high percentage of muropeptides remains uncross-linked. The second mechanism may be the more significant in most cases.